Photoprotective activities of Lignosus rhinocerus in UV-irradiated human keratinocytes - Lim, Hui Sin *; Samson Eugin, Simon *; Yow, Yoon Yen *; Saidur, Rahman *; Tan, Kuan Onn * (Elsevier, 2022)
Ethnopharmacological relevance Lignosus rhinocerus, also known as Tiger Milk Mushroom has been used traditionally to treat a variety of human conditions, including asthma, diabetes, respiratory disease, skin allergy, and food poisoning. The reported activities of Lignosus rhinocerus extracts include anti-inflammatory, anti-oxidant, anti-asthmatic, anti-microbial, anti-cancer, neuroprotection, and immune modulation effects. However, its effect on human skin is not well documented, including human skin exposed to ultraviolet light (UV). Exposure to UV can trigger various cellular responses, including inflammation, oxidative stress, DNA damage, cell death, and cellular aging.